Integrasi Nilai Pendidikan Islam dan Budaya Lokal dalam Tradisi Naik Ayun pada Masyarakat Bugis - Casrameko, Casrameko; Shalihah, Diar (IEMJ: Islamic Education and Management Journal, 2024)
This research aims to reveal the values of Islamic education management in the Naik Ayun tradition among the Bugis community in Pontianak. The Naik Ayun tradition is a cultural ritual performed for newborn babies as a form of thanksgiving and prayer so that they grow up to be pious and useful children for religion, family and society. In its implementation, this tradition is not only a cultural heritage, but also contains Islamic values. This research uses a qualitative approach with a descriptive method. Data collection techniques were conducted through in-depth interviews, participatory observation, and documentation. The results showed that the Naik Ayun tradition contains Islamic education values that are integrated symbolically and practically. First, the cultivation of the value of tawhid through the recitation of prayers and verses of the Qur'an. Second, the value of gratitude in the form of alms and banquets. Third, the value of moral and social education through the role of the extended family and community in the implementation of the tradition. Fourth, the value of preserving local culture in harmony with Islamic teachings. This research confirms that the Naik Ayun tradition can be an effective non-formal Islamic education medium in shaping children's character from an early age in the context of local culture.